Mechanically Durable and Flexible Thermoelectric Films from PEDOT:PSS/PVA/Bi0.5Sb1.5Te3 Nanocomposites. (28th February 2017) - Zhang, Ting; Li, Kaiwei; Li, Chengchao; Ma, Shaoyang; Hng, Huey Hoon; Wei, Lei
Abstract : Advances in organic thermoelectric materials have focused on the enhancement of mechanical property to address the limitations and needs of forming flexible and free‐standing films for the application of flexible/wearable thermoelectric devices. Herein, thermoelectric nanocomposite films are fabricated based on conductive polymer poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), plastic reinforcer polyvinyl alcohol (PVA), and inorganic Bi0.5 Sb1.5 Te3 thermoelectric nanocrystals with various contents. The resulting PEDOT:PSS/PVA/Bi0.5 Sb1.5 Te3 nanocomposite films exhibit a power factor of 47.7 µW m −1 K −2 and a ZT value of 0.05 at 300 K. More importantly, they are mechanically tough, yet very flexible with a tensile strength of 79.3 MPa and a fracture strain of 32.4%, which is sufficient to meet the required mechanical properties of textile manufacturing and body movements for flexible thermoelectric films, thus providing a substantial impact on future developments of flexible/wearable energy generation devices. Abstract : Flexible and free‐standing PEDOT:PSS/PVA/Bi0.5 Sb1.5 Te3 nanocomposite film is fabricated with good thermoelectric and mechanical properties. The resulting film offers a ZT value of 0.05 at 300 K, and exhibits large tensile strength of 100.8 MPa and fraction strain of 63.1%.